2007
DOI: 10.1073/pnas.0603762104
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the structure of SET/TAF-Iβ/INHAT and its histone chaperone activity

Abstract: Histone chaperones assemble and disassemble nucleosomes in an ATP-independent manner and thus regulate the most fundamental step in the alteration of chromatin structure. The molecular mechanisms underlying histone chaperone activity remain unclear. To gain insights into these mechanisms, we solved the crystal struc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
185
0
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(209 citation statements)
references
References 52 publications
8
185
0
10
Order By: Relevance
“…Indeed, it encodes a multifunctional nuclear protein expressed in various human cell lines and tissues and involved in several pathways. 23 It interacts with SETBP1, SET-binding protein, whose haploinsufficiency had been reported in association with ID and speech delay. 24 Recently, a de novo frameshift deletion resulting in a premature stop codon in SET has been identified in a patient with congenital microcephaly, normal brain and moderate ID.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it encodes a multifunctional nuclear protein expressed in various human cell lines and tissues and involved in several pathways. 23 It interacts with SETBP1, SET-binding protein, whose haploinsufficiency had been reported in association with ID and speech delay. 24 Recently, a de novo frameshift deletion resulting in a premature stop codon in SET has been identified in a patient with congenital microcephaly, normal brain and moderate ID.…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal 24 amino acids of human SET/ TAF-I are not required for many activities such as DNA replication and transcription stimulation (Miyaji-Yamaguchi et al, 1999), but the residues Thr23 and Ser24 are involved in a long -helix ( 2) which has a stable structure in the crystal structure of SET/TAF-I ÁC (PDB code 2e50; Muto et al, 2007). Therefore, a truncated form of SET/TAF-I was designed for crystallization experiments that lacked 22 residues from the N-terminus.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular replacement was carried out with MOLREP (Vagin & Teplyakov, 1997) in the CCP4 suite (Collaborative Computational Project, Number 4, 1994) using the structure of residues 23-225 of H. sapiens SET/TAF-I ÁC (PDB code 2e50; Muto et al, 2007) as a search model. Furthermore, systematic absences indicated that the SET/TAF-I ÁN crystal belonged to space group P4 3 2 1 2 or its enantiomer P4 1 2 1 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations